Organizational capacity building of SMA Muhammadiyah III Yogyakarta through effective communication - Adhianty Nurjanah; Sri Nabawiyati Nurul Makiyah (Universitas Muhammadiyah Magelang, 2023)
Good communication between teachers and students will create a fun teaching and learning process and establish positive cooperation in efforts to develop school organizational capacity. In order to achieve this, the community service aims to support teachers in the learning process through effective organizational communication training. The implementation of this program begins with an initial assessment followed by increasing awareness regarding leadership and training in organizational capacity building with an effective organizational communication approach. The results of this program shows an increase in understanding and application of the importance of communication skills in school organizations by 85%. At the end of the program, a grant was given in the form of a sound system as an internal communication medium.